Self-assembly of mixed Pt and Au nanoparticles on PDDA-functionalized graphene as effective electrocatalysts for formic acid oxidation of fuel cells - Wang, S.; Wang, X.; Jiang, San Ping (Royal Society of Chemistry, 2011)
Pt and Au nanoparticles with controlled Pt :Au molar ratios and PtAu nanoparticle loadings were successfully self-assembled onto poly(diallyldimethylammonium chloride) (PDDA)-functionalized graphene (PDDA-G) as highly effective electrocatalysts for formic acid oxidation in direct formic acid fuel cells (DFAFCs). The simultaneously assembled Pt and Au nanoparticles on PDDA-G showed superb electrocatalytic activity for HCOOH oxidation, and the current density associated with the preferred dehydrogenation pathway for the direct formation of CO2 through HCOOH oxidation on a Pt1Au8/PDDA-G (i.e., a Pt :Au ratio of 1 : 8) is 32 times higher than on monometallic Pt/PDDA-G. The main function of the Au in the mixed Pt and Au nanoparticles on PDDA-G is to facilitate the first electron transfer from HCOOH to HCOOads and the effective spillover of HCOOads from Au to Pt nanoparticles, where HCOOads is further oxidized to CO2. The Pt :Au molar ratio and PtAu nanoparticle loading on PDDA-G supports are the two critical factors to achieve excellent electrocatalytic activity of PtAu/PDDA-G catalysts for the HCOOH oxidation reactions.